2009
DOI: 10.1002/jbio.200910059
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of vascular structures and skin bruises using hyperspectral imaging, image analysis and diffusion theory

Abstract: Hyperspectral imaging, image analysis and diffusion theory were used to visualize skin vasculature and to monitor the development of fresh skin bruises. Bruises were inflicted in a porcine model, and the development of the hemorrhage was monitored using white light hyperspectral imaging (400-1000 nm). Hyperspectral images from human volunteers were also included in the study. Statistical image analysis was used to classify bruised regions and to visualize the skin vasculature. Biopsies were collected from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 22 publications
0
68
0
2
Order By: Relevance
“…The roles of other parameters such as immunohistochemistry, hyperspectral imaging, and magnetic resonance imaging (MRI) in helping to date bruises are yet to be established [18][19][20][21].…”
mentioning
confidence: 99%
“…The roles of other parameters such as immunohistochemistry, hyperspectral imaging, and magnetic resonance imaging (MRI) in helping to date bruises are yet to be established [18][19][20][21].…”
mentioning
confidence: 99%
“…[43][44][45] Spectral reflectance from skin is interpreted as contributions from the epidermal layer (melanin), as well as upper and lower dermal layers, each of which contain differing concentration of hemoglobin species. The resulting calculations of StO 2 values from this study support the results presented by these other groups.…”
Section: Discussionmentioning
confidence: 99%
“…Payne et al showed the possibility to use HSI to differentiate pure blood from blood with bilirubin based on these spectral features [45]. Randeberg et al presented hyperspectral images of bruises on porcine and human skin [46]. They used minimum noise fraction transform, a statistical method similar to PCA, to classify the injuries.…”
Section: Other Tracesmentioning
confidence: 99%